Influence of countermovement depth on the countermovement jump-derived reactive strength index modified - Pérez-Castilla, A.; Weakley, J.; Garcia-Pinillos, F.; Rojas, J.; Garcia-Ramos, A. (European Journal of Sport Science, 2020)
This study aimed to investigate the effect of countermovement depth on the magnitude of the countermovement jump (CMJ) derived reactive strength index modified (RSImod), and to compare the RSImod between the CMJ performed with a self-preferred knee flexion angle (CMJpref) and the CMJ performed from a pre-determined knee flexion angle (CMJrefer) with the countermovement depth more similar to the CMJpref. Sixteen subjects (11 males and 5 females; age 25.1±6.3 years, body mass 69.7±10.2 kg, body height 172.9±8.1 m) randomly performed in a single session the CMJpref and CMJs from five pre-determined knee flexion angles (60°, 75°, 90°, 105°, and 120°). Our results showed that lower knee flexion angles were generally associated with greater RSImod values with the CMJ performed at 60° showing the greatest RSImod (P=0.049; effect size [ES] range=0.19-0.63). The greatest RSImod for the CMJ performed at 60° was caused by the proportionally lower values of the time to take-off (ES range=0.65-1.91) compared to the decrease observed in jump height (ES range=0.11-0.25). The RSImod was higher for the CMJpref compared to the CMJrefer (P<0.001; ES=0.34) due to a higher jump height (P=0.021; ES=0.14) and reduced time to take-off (P<0.001; ES=0.85). These results indicate that practitioners should be careful when interpreting an individual`s changes in RSImod when the countermovement depth is not similar across the testing sessions. However, since the use of pre-determined knee flexion angles negatively impacts the RSImod, we encourage practitioners to use the CMJpref but only compare the RSImod when CMJs are performed using consistent countermovement depths.